High-concentration and high-flowability full-tailing filling material based on air microbeads and filling method of high-concentration and high-flowability full-tailing filling material

By using the combination of air bead stabilizer and interface agent in mine filling technology, the problems of separating, water excretion and settlement of cemented filling slurry during the transport process are solved, and efficient and low-cost filling effect is achieved, improving filling body strength and tailings utilization rate.

CN119163467APending Publication Date: 2024-12-20SHANDONG ELECTRIC POWER CONSTR NO 2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411366084.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-20
Patent Text Reader

Abstract

The invention discloses a high-concentration and high-fluidity full-tailing filling material based on air microbeads, which comprises the following components: mineral separation tailings, a cementing material, water, a liquid-solid interface agent, a gas-liquid interface agent, an air microbead stabilizer and an air microbead removal liquid, and also discloses a filling method of the filling material. After the cementing material and the full-tailing filling material are mixed, the fluidity of the material becomes poor, so that the air microbeads which are obtained through the air microbead generation liquid and have relatively long stability are specially added, and the material can be in a high-fluidity colloidal state before being filled; the colloidal filling slurry is filled with the air microbeads and does not bleed, separate, precipitate and block a filling pipeline in the filling and conveying process, and after filling and injection are completed, the colloidal filling slurry can be rapidly flocculated and deposited along with breaking of the air microbeads, so that a filling body is primarily dense, and higher strength is obtained along with solidification of a cementing material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of mine filling and restoration, in particular to a high-concentration and high-fluidity full tailings filling material based on air microspheres, and also to a filling method of the material. Background Art

[0002] In order to ensure the safety of the mining process, obtain mineral resources more fully, or to deal with the waste generated in the mining project and protect the ecological environment of the mining area and its surroundings, most mines must carry out filling operations in tunnels and pits during or after the mining process. At present, mine filling operations can be roughly divided into three types: dry filling, water-sand filling and cemented filling.

[0003] Among them, dry filling is the use of mechanical transportation to backfill waste rock, stockpiled tailings, construction waste, etc. near the mine into the goaf. Its advantages are low technical difficulty, and its disadvantages are low efficiency and high cost. It has now been gradually eliminated; water-sand filling is the use of a large amount of water power to send sand into the area to be filled. After drainage and sedimentation, the sand completes the filling of the goaf. Its advantages are large filling capacity, high efficiency and relatively low cost. Its disadvantages are strict requirements on the particle size range of sand materials, and it cannot make full use of industrial and mining waste such as tailings with relatively fine particle sizes. It also consumes a lot of water and has a high ecological cost. It is now rarely used; cemented filling mainly utilizes tailings from the ore dressing plant, mixes it with a certain amount of cementing material to prepare a filling slurry with a certain concentration, and returns the filling slurry to the goaf of the mine, relying on the solidification effect of the cementing material to form a filling body with a certain strength. Since this filling process can use the entire tailings for backfilling, it has significant ecological benefits and has become the mainstream method of mine filling operations today.

[0004] According to the concentration and fluid characteristics of the filling slurry, cementing filling can be divided into two types: slurry filling and paste filling. Among them, the slurry concentration of slurry filling is generally not higher than 65%, and the slurry still exists in the form of solid-liquid two phases during transportation. The advantages are that the flow resistance of the slurry is relatively small, gravity flow or low-pressure flow transportation can be achieved, the utilization rate of tailings is relatively high, and the production equipment is relatively simple. The disadvantages are that due to the large water-cement ratio, the slurry is prone to segregation, bleeding, and sedimentation, which not only easily causes pipeline blockage, but also makes it difficult to improve the strength of the filling body, especially its early strength; compared with slurry filling, the concentration of paste filling is higher (generally greater than 75%) and the water-cement ratio is lower. The paste presents a single-phase plunger structure flow state in the conveying pipeline, with almost no segregation, no bleeding, and no sedimentation. The strength of the filling body, especially the early strength, is relatively high. The disadvantages are that the amount of cementing material used is large, and a certain amount of coarse aggregate needs to be added, resulting in low tailings utilization, large flow resistance, high transportation energy consumption, complex production equipment and high technical requirements.

[0005] Therefore, finding a filling slurry that has good fluidity, does not separate or seep water during transportation, can reduce the amount of cementing materials used, improve the utilization rate of tailings, and ensure the early strength of the filling body has become a technical key that needs to be solved urgently. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a high-concentration and high-fluidity full tailings filling material based on air microspheres that can fully utilize the waste materials discharged from mines, use as little binder as possible, simplify the production process, reduce the consumption of energy and equipment, and achieve high efficiency and good filling effect.

[0007] In order to solve the above technical problems, the technical solution of the present invention is: a high-concentration and high-fluidity full tailings filling material based on air microspheres, comprising the following components: ore dressing tailings, gelling material, water, liquid-solid interface agent, gas-liquid interface agent, air microsphere stabilizer, and air microsphere removing liquid.

[0008] As a preferred technical solution, the ore dressing tailings come from waste materials of a ore dressing plant, a coal washing plant or / and a stone crushing plant, and the ore dressing tailings are whole tailings and / or separated tailings.

[0009] As a preferred technical solution, the ore dressing tailings include solid tailings, paste tailings and / or fluid tailings, and the concentration of the solid tailings, the paste tailings and / or the fluid tailings when used is greater than 60%.

[0010] As a preferred technical solution, the cementitious material includes one or a mixture of any proportion of two or more of cement, lime, gypsum, carbide slag, red mud, fly ash, granulated blast furnace slag, and ground slag.

[0011] As a preferred technical solution, the water is ordinary water and / or wastewater discharged from a mine.

[0012] As a preferred technical solution, the liquid-solid interface agent includes one or a mixture of any two or more of calcium lignin sulfonate, sodium naphthalenesulfonic acid formaldehyde condensation, sulfonated melamine formaldehyde resin, aminophenol formaldehyde condensation sulfonate, aliphatic hydroxy sulfonate, and polycarboxylic acid.

[0013] As a preferred technical solution, the gas-liquid interface agent includes one or a mixture of any two or more of sodium rosin acid, sodium rosin thermal polycondensation, sodium alkylbenzene sulfonate, sodium alkylphenol polyoxyethylene ether sulfate, sodium fatty alcohol polyoxyethylene ether sulfate, tea saponin, triterpenoid saponin, and hydrolyzed protein;

[0014] The air microsphere stabilizer comprises one or a mixture of any proportion of polyacrylamide, polyvinyl alcohol, silicone resin polyether, bone glue, hide glue, and dodecyl methylamine oxide.

[0015] As a preferred technical solution, the air microbead removing liquid includes one or a mixture of any proportion of two or more of oxidized silane, emulsified silicone oil, polyoxypropylene glycol ether, fatty amine, fatty alcohol, diesel, waste animal oil, and waste vegetable oil.

[0016] The present invention also provides a filling method of a high-concentration and high-fluidity full tailings filling material based on air microspheres, comprising the following steps:

[0017] Step 1: Pretreatment of ore dressing tailings

[0018] The ore dressing tailings with a concentration of less than 60% are introduced into a deep cone concentrator or a plate and frame filter press for dehydration treatment to make the concentration greater than 60%, or the concentration of the ore dressing tailings is increased to more than 60% by material mixing;

[0019] Step 2: Prepare air microsphere generating liquid

[0020] The gas-liquid interface agent and the water are mixed and stirred at a weight ratio of 1:1 to 1:1.5, and the water is at room temperature until the gas-liquid interface agent is completely dissolved to obtain a gas-liquid interface agent mother solution;

[0021] Take the air microsphere stabilizer and the water, wherein the weight ratio of the air microsphere stabilizer to the water is 1:5 to 1:8, heat the water to 40 to 50° C. and mix it with the air microsphere stabilizer, soak the air microsphere stabilizer in water to swell it, and obtain a colloid by stirring, which is the mother solution of the air microsphere stabilizer;

[0022] The mother solution of the gas-liquid interface agent and the mother solution of the air microsphere stabilizer are mixed in a weight ratio of 1:1 to 1:1.5 to obtain a mixed mother solution, and the mixed mother solution is diluted with 40 to 45 times the volume of water to obtain the air microsphere generating solution;

[0023] Step 3: Preparation of high-concentration and high-fluidity tailings filling materials

[0024] The ore dressing tailings pretreated in step 1 are introduced into a continuous mixer or a stirring tank for stirring. During the stirring process, the cementitious material is continuously added at a ratio of 6% to 10% of the weight of the ore dressing tailings by another conveying device. At the same time, the liquid-solid interface agent at a ratio of 0.1% to 1.0% of the weight of the cementitious material is continuously added into the above-mentioned continuous mixer or stirring tank through a metering and conveying device. Through continuous stirring, the ore dressing tailings, the cementitious material and the liquid-solid interface agent are gradually mixed and uniformly during the moving process to obtain a full tailings cementitious paste, and then the full tailings cementitious paste is collected in a pre-pump stirring tank;

[0025] Using a liquid flow pump to extract the air microbead generation liquid and send it to an air microbead generator, and using the air microbead generator to obtain air microbeads;

[0026] The air microspheres sprayed from the air microsphere generator are mixed into the whole tailings cement paste in the mixing tank before the pump, and the volume ratio of the whole tailings cement paste to the air microspheres is 10:1 to 10:3, so as to obtain a stable, rheological, non-bleeding, non-segregating high-concentration and high-fluidity whole tailings filling material;

[0027] Step 4: Filling

[0028] Relying on gravity or pumping force, the high-concentration and high-fluidity full tailings filling material is transported to the tunnel or mine pit to be filled through the filling pipeline;

[0029] Step 5: Filling and Control

[0030] Observations were conducted during the transportation of the high-concentration and high-fluidity full tailings filling material. The normal state of the high-concentration and high-fluidity full tailings filling material is no precipitation, no segregation, and no water seepage. After filling in place, precipitation and solidification will occur. A trace amount of water seepage is allowed, but obvious segregation is not allowed. By matching the ratio of the gas-liquid interface agent and the air microsphere stabilizer in step 2, the air microspheres will not burst before the high-concentration and high-fluidity full tailings filling material is filled in place, and will burst within 6 hours after filling in place.

[0031] As a preferred technical solution, in step five, if it is observed that the air microspheres cannot be shattered within 6 hours after the high-concentration and high-fluidity full tailings filling material is filled in place, the air microsphere scavenger is mixed into the outlet of the filling pipe, and the amount of the air microsphere scavenger is 0.001‰ to 0.01‰ of the weight of the high-concentration and high-fluidity full tailings filling material. The more the amount used, the faster the air microspheres shatter.

[0032] Due to the adoption of the above-mentioned technical scheme, the present invention has the following beneficial effects: after the cementitious material is mixed with the whole tailings filling material, the fluidity of the material will deteriorate, so air microspheres with longer stability obtained by air microsphere generating liquid are specially added to enable the material to present a highly fluid colloid before filling, and will not exude water, separate, precipitate, or block the filling pipeline during filling and transportation. After the filling and injection are completed, as the air microspheres burst, the colloidal filling slurry will quickly flocculate and precipitate, so that the filling body reaches a preliminary density, and obtains higher strength as the cementitious material solidifies. DETAILED DESCRIPTION

[0033] The present invention will be further described below in conjunction with the embodiments. In the following detailed description, only certain exemplary embodiments of the present invention are described by way of illustration. Needless to say, those of ordinary skill in the art will appreciate that the described embodiments may be modified in a variety of ways without departing from the spirit and scope of the present invention. Therefore, the description is illustrative in nature and is not intended to limit the scope of protection of the claims.

[0034] A high-concentration and high-fluidity full tailings filling material based on air microspheres, used for filling tunnels or mines after ore mining, specifically includes the following components: ore dressing tailings, gelling materials, water, liquid-solid interface agent, gas-liquid interface agent, air microsphere stabilizer, and air microsphere scavenging liquid. Among them, the ore dressing tailings come from waste materials of ore dressing plants, coal washing plants and / or stone crushing plants. The ore dressing tailings are full tailings and / or sorting tailings. Of course, they are not limited to the waste materials generated in the above-mentioned plant areas. The ore dressing tailings formed in the production process of other enterprises using ore materials can be used. The full tailings refer to all tailings discharged from the mine, and the sorting tailings refer to the part of tailings that are abandoned after the tailings discharged from the mine are properly sorted. The present embodiment preferably uses the full tailings.

[0035] Of course, the ore dressing tailings can also be set as solid tailings, paste tailings or / and fluid tailings, and the concentrations of the solid tailings, the paste tailings or / and the fluid tailings when used are all greater than 60%. Generally, the concentration of the solid tailings is greater than 75%, the concentration of the paste tailings is 60% to 75%, and the concentration of the fluid tailings is less than 60%. Therefore, the fluid tailings needs to be increased to a concentration of more than 60% when used. Specifically, the excess water in the ore can be removed by a dehydration process, or it can be mixed with the solid tailings and the paste tailings in stock to adjust its concentration to greater than 60%.

[0036] The cementitious material includes one or more of cement (such as ordinary Portland cement), lime, gypsum, carbide slag, red mud, fly ash, granulated blast furnace slag, and ground slag in any proportion. The water is ordinary water and / or wastewater discharged from the mine, preferably wastewater discharged from the mine. When the wastewater is insufficient, ordinary water is used to supplement it to save water resources. After the cementitious material meets water, it will be in a fluid state for a period of time at first, and gradually transition to a plastic state as time goes by, and then gradually form a solidified state, and form a material with a certain strength, which cooperates with the mineral processing tailings to achieve compact filling of goafs, etc.

[0037] The liquid-solid interface agent includes one or a mixture of any two or more of calcium lignin sulfonate, sodium naphthalenesulfonic acid formaldehyde condensation, sulfonated melamine formaldehyde resin, aminophenol formaldehyde condensation sulfonate, aliphatic hydroxy sulfonate, and polycarboxylic acid. The liquid-solid interface agent can significantly reduce the surface tension of the liquid near the solid particles of the ore dressing tailings, so that it is easier to be wetted by the liquid, and at the same time, it can also prevent the solid particles from forming a flocculated structure and constraining part of the liquid, so that the solid particles are easier to disperse, and the fluidity effect of the tailings is further improved.

[0038] The gas-liquid interface agent includes one or more of sodium rosin acid, sodium rosin thermal polycondensation, sodium alkylbenzene sulfonate, sodium alkylphenol polyoxyethylene ether sulfate, sodium fatty alcohol polyoxyethylene ether sulfate, tea saponin, triterpenoid saponin, and hydrolyzed protein, and a mixture of any proportion. The gas-liquid interface agent can reduce the surface tension of the liquid. When the liquid phase contains the interface agent and is mixed and stirred with air, a large amount of small, stable, elastic spherical or nearly spherical bubbles, i.e., air microspheres, can be formed inside the liquid. The air microsphere stabilizer includes one or more of polyacrylamide, polyvinyl alcohol, silicone resin polyether, bone glue, leather glue, and dodecyl methylamine oxide, and a mixture of any proportion. Its function is to prolong the maintenance time of the formed air microspheres to enhance their effect in the material, even if the material can present a high-fluidity colloidal state before filling, and does not ooze, separate, precipitate, or block the filling pipeline during filling and transportation. Generally, each 1L of the air microsphere generating liquid can generate 0.5 to 0.7 m 3 The air microspheres are affected by many factors such as temperature, air pressure, and mechanical equipment parameters, so that the volume of the air microspheres and the volume of the air microsphere generating liquid are not always in equal proportion. Therefore, the amount of the air microsphere generating liquid can be adjusted in time.

[0039] The present embodiment also provides an air micro-balloon removal liquid, which can quickly break and disappear the air micro-balloons therein after the material is filled to ensure the compactness of the filling, and the amount can be adjusted in time by observation. The air micro-balloon removal liquid includes one or a mixture of any proportion of silane oxide, emulsified silicone oil, polyoxypropylene glycol ether, fatty amine, fatty alcohol, diesel, waste animal oil, and waste vegetable oil.

[0040] This embodiment also provides a filling method of a high-concentration and high-fluidity full tailings filling material based on air microspheres, comprising the following steps:

[0041] Step 1: Pretreatment of ore dressing tailings

[0042] The ore dressing tailings with a concentration of less than 60% are introduced into a deep cone concentrator or a plate and frame filter press for dehydration treatment to make the concentration greater than 60%, or the concentration of the ore dressing tailings is increased to more than 60% by material mixing;

[0043] Step 2: Prepare air microbead generation liquid

[0044] The gas-liquid interface agent and the water are mixed and stirred at a weight ratio of 1:1 to 1:1.5, and the water is at room temperature until the gas-liquid interface agent is completely dissolved to obtain a gas-liquid interface agent mother solution;

[0045] Take the air microsphere stabilizer and the water, wherein the weight ratio of the air microsphere stabilizer to the water is 1:5 to 1:8, heat the water to 40 to 50° C. and mix it with the air microsphere stabilizer, soak the air microsphere stabilizer in water to swell it, and obtain a colloid by stirring, which is the mother solution of the air microsphere stabilizer;

[0046] The mother solution of the gas-liquid interface agent and the mother solution of the air microsphere stabilizer are mixed in a weight ratio of 1:1 to 1:1.5 to obtain a mixed mother solution, and the mixed mother solution is diluted with 40 to 45 times the volume of water to obtain the air microsphere generating solution;

[0047] Step 3: Preparation of high-concentration and high-fluidity tailings filling materials

[0048] The ore dressing tailings pretreated in step 1 are introduced into a continuous mixer or a stirring tank for stirring. During the stirring process, the cementitious material is continuously added at a ratio of 6% to 10% of the weight of the ore dressing tailings by another conveying device. At the same time, the liquid-solid interface agent at a ratio of 0.1% to 1.0% of the weight of the cementitious material is continuously added into the above-mentioned continuous mixer or stirring tank through a metering and conveying device. Through continuous stirring, the ore dressing tailings, the cementitious material and the liquid-solid interface agent are gradually mixed and uniformly during the moving process to obtain a full tailings cementitious paste, and then the full tailings cementitious paste is collected in a pre-pump stirring tank;

[0049] Using a liquid flow pump to extract the air microbead generation liquid and send it to an air microbead generator, and using the air microbead generator to obtain air microbeads;

[0050] The air microspheres sprayed from the air microsphere generator are mixed into the whole tailings cement paste in the mixing tank before the pump, and the volume ratio of the whole tailings cement paste to the air microspheres is 10:1 to 10:3, so as to obtain a stable, rheological, non-bleeding, non-segregating high-concentration and high-fluidity whole tailings filling material;

[0051] Step 4: Filling

[0052] Relying on gravity or pumping force, the high-concentration and high-fluidity full tailings filling material is transported to the tunnel or mine pit to be filled through the filling pipeline;

[0053] Step 5: Filling and Control

[0054] Observations were conducted during the transportation of the high-concentration and high-fluidity full tailings filling material. The high-concentration and high-fluidity full tailings filling material is in a normal state of having high fluidity, viscosity and lubricity. It does not precipitate, segregate or seep water during transportation. Precipitation and solidification will occur after filling in place. A trace amount of water seepage is allowed, but obvious segregation is not allowed. By matching the ratio of the gas-liquid interface agent and the air microsphere stabilizer in step 2, the air microspheres will not burst before the high-concentration and high-fluidity full tailings filling material is filled in place, but will burst quickly after filling in place, generally within 6 hours, to achieve high-density filling.

[0055] In step five, if it is observed that the air microspheres cannot be shattered within 6 hours after the high-concentration and high-fluidity full tailings filling material is filled in place, the air microsphere scavenger is mixed into the outlet of the filling pipe. The amount of the air microsphere scavenger is 0.001‰ to 0.01‰ of the weight of the high-concentration and high-fluidity full tailings filling material. The more the amount used, the faster the air microspheres shatter. If the air microspheres cannot be shattered quickly as described above, the air microsphere scavenger may not be used.

[0056] During the implementation of the above steps of the filling method of this embodiment, the dosage ratio of the components of mineral processing tailings, cementitious material, water, liquid-solid interface agent, gas-liquid interface agent, and air microbead stabilizer is clearly defined by limiting the amount of each component added.

[0057] Embodiment 1:

[0058] The mineral processing tailings are whole tailings for gold processing. Based on the gold processing process, the mineral processing tailings contain a large amount of water to form whole tailings slurry. The initial discharge concentration is generally around 15%. After passing through a primary thickener, the underflow concentration is increased to 55%. After adding about 30% volume of dry tailings from a filter press, the mass concentration of the whole tailings slurry is increased to 72%±3%.

[0059] The whole tailings slurry: 42.5 grade ordinary silicate cement has a dry matter weight ratio of 9:1, and 1% of the cement weight of the liquid-solid interface agent is added to form a gelled tailings slurry, i.e. the whole tailings filling material, and flows continuously in the stirring tank. The theoretical conveying capacity of the whole tailings filling material is 90m 3 / h, use a 20m 3 / h air microsphere generator continuously sprays the air microspheres into the stirring tank, so that the volume ratio of the whole tailings filling material to the air microspheres is about 5:1.

[0060] In the application scenario of this embodiment, the whole tailings filling material is fed by a slurry pump, and the filling pipeline is transported by a φ100mm polymer pipe. The vertical transportation distance is 400m, the horizontal transportation distance is 2.4km, and seven pipeline elbows are passed during transportation.

[0061] The actual measured effect of this embodiment is: the actual maximum conveying capacity is 80m 3 / h, pump pressure 7-8MPa, no pipeline blockage or other faults occurred after 30 days of operation, the air beads disappeared automatically within 5 hours after the filling body was in place, the filling body slurry was self-compacting, and basically lost its fluidity in 24 hours, the compressive strength was 0.24MPa at 3 days, 0.87MPa at 7 days, and 1.43MPa at 28 days, which met the acceptance conditions.

[0062] Embodiment 2:

[0063] The mineral processing tailings are limestone tailings. After the full tailings filling material is obtained in the sedimentation tank by using a double-extraction mixer according to the above steps, the air microspheres equivalent to about 20% of the volume of the sediment are sprayed into the sedimentation tank mud, which greatly reduces the viscosity of the mud, greatly improves the fluidity of the mud, reduces the pumping resistance, and can be smoothly transported to the backfill pit using an ordinary slurry pump.

[0064] Before the improvement of this embodiment was adopted, the concentration of the mud discharged from the screening and washing system was 25% to 28%, the particle size of the stone powder was all less than 0.25mm, and the ultra-fine sand particles with a particle size of 0.075mm accounted for more than 77% of the total mass. After natural sedimentation in the sedimentation tank, the concentration of the bottom mud was 60% to 65%. If pumping was used for backfilling, it would be extremely difficult to transport due to insufficient fluidity; it was necessary to switch to using four plate and frame filter presses to filter, so that the moisture content of the mud cake was reduced to 15% to 18%, and then the mine pit was backfilled by car, and the transportation cost was extremely high. After the case was put into trial use, the comprehensive backfilling cost was reduced by more than 50%.

[0065] Embodiment 3:

[0066] The beneficiation tailings are copper tailings. Based on the copper beneficiation process, the beneficiation tailings contain a large amount of water to form a whole tailings slurry. The initial discharge concentration is generally about 23%. A first-stage thickener is used to increase the underflow concentration to about 52%, and then a deep cone thickener is used to further dehydrate the water to increase the concentration to 78% to 80%. The whole tailings slurry: cement is mixed into a paste in a volume ratio of 9:1, and then a plunger pump is used for paste-type cementing filling. The pipeline resistance is recorded to be 14.3 kPa / m; the liquid-solid interface agent is added to the mixer, and the air microbeads equivalent to 20% of the volume of the original filling paste are sprayed into the mixer while adding cement, so that the fluidity of the paste is significantly improved. Under the same experimental conditions, the pipeline resistance is detected to drop from 14.3 kPa / m to 2.4 to 2.5 kPa / m, and the transportation energy consumption is saved by up to 40%.

[0067] The present invention is constructed based on existing scientific principles such as the hydration-hardening theory of cementitious materials, the friction and resistance theory of confined fluids, the mechanics of gas-liquid and liquid-solid interfaces, colloid stability and flocculation chemistry, etc. Specifically, according to the hydration-hardening principle of cementitious materials, the strength of the cementitious hardened body depends not only on the content of cementitious materials, but more importantly on the ratio of water to cementitious materials. Under the condition of the same amount of cementitious materials, the smaller the water-to-binder ratio, the higher the strength of the gel, but at the same time, the worse the fluidity of the slurry before solidification. In order to improve the fluidity of the slurry under low water-cement ratio conditions and reduce the friction resistance between its inside and outside, air microspheres with relatively long stability can be introduced into the filling slurry; and the stability and collapse of the air microspheres can be flexibly adjusted by factors such as the molecular structure, molecular weight, and concentration of the surfactant, so that the whole tailings filling slurry can present a highly fluid colloid state before filling, and will not seep water, separate, precipitate, or clog the pipeline during transportation. After the filling and injection is completed, as the air microspheres collapse, the colloidal filling slurry will quickly flocculate and settle, so that the filling body reaches an initial density and obtains higher strength as the cementitious material solidifies.

[0068] The description of the present invention is given for the purpose of illustration and description, and is not intended to be exhaustive or to limit the invention to the disclosed form. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described in order to better illustrate the principles and practical applications of the present invention and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for particular uses.

Claims

1. A high-concentration and high-fluidity full tailings filling material based on air microspheres, characterized in that: The invention comprises the following components: ore dressing tailings, cementitious materials, water, liquid-solid interface agent, gas-liquid interface agent, air micro-balloon stabilizer and air micro-balloon removing liquid.

2. A high-concentration and high-fluidity full tailings filling material based on air microspheres as claimed in claim 1, characterized in that: The ore dressing tailings are waste materials from ore dressing plants, coal washing plants and / or stone crushing plants, and the ore dressing tailings are whole tailings and / or separated tailings.

3. The high-concentration and high-fluidity full tailings filling material based on air microspheres as claimed in claim 1, characterized in that: The ore dressing tailings include solid tailings, paste tailings and / or fluid tailings. The concentration of the solid tailings, the paste tailings and / or the fluid tailings when used is greater than 60%.

4. The high-concentration and high-fluidity full tailings filling material based on air microspheres as claimed in claim 1, characterized in that: The cementitious material comprises one or a mixture of any proportion of two or more of cement, lime, gypsum, carbide slag, red mud, fly ash, granulated blast furnace slag and ground slag.

5. The high-concentration and high-fluidity full tailings filling material based on air microspheres as claimed in claim 1, characterized in that: The water is ordinary water and / or waste water discharged from a mine.

6. The high-concentration and high-fluidity full tailings filling material based on air microspheres as claimed in claim 1, characterized in that: The liquid-solid interface agent includes one or a mixture of any two or more of calcium lignin sulfonate, sodium naphthalenesulfonic acid formaldehyde condensation, sulfonated melamine formaldehyde resin, aminophenol formaldehyde condensation sulfonate, aliphatic hydroxy sulfonate, and polycarboxylic acid.

7. The high-concentration and high-fluidity full tailings filling material based on air microspheres as claimed in claim 1, characterized in that: The gas-liquid interface agent includes one or a mixture of any two or more of sodium rosin acid sodium, sodium rosin thermal polycondensation, sodium alkylbenzene sulfonate, sodium alkylphenol polyoxyethylene ether sulfate, sodium fatty alcohol polyoxyethylene ether sulfate, tea saponin, triterpenoid saponin, and hydrolyzed protein; The air microsphere stabilizer comprises one or a mixture of any proportion of polyacrylamide, polyvinyl alcohol, silicone resin polyether, bone glue, hide glue, and dodecyl methylamine oxide.

8. The high-concentration and high-fluidity full tailings filling material based on air microspheres as claimed in claim 1, characterized in that: The air micro-beads removing liquid comprises one or a mixture of any proportion of oxidized silane, emulsified silicone oil, polyoxypropylene glycol ether, fatty amine, fatty alcohol, diesel, waste animal oil, and waste vegetable oil.

9. A filling method of a high-concentration and high-fluidity full tailings filling material based on air microspheres as claimed in claim 8, characterized in that: The following steps are included: Step 1: Pretreatment of ore dressing tailings The ore dressing tailings with a concentration of less than 60% are introduced into a deep cone concentrator or a plate and frame filter press for dehydration treatment to make the concentration greater than 60%, or the concentration of the ore dressing tailings is increased to more than 60% by material mixing; Step 2: Prepare air microsphere generating liquid The gas-liquid interface agent and the water are mixed and stirred at a weight ratio of 1:1 to 1:1.5, and the water is at room temperature until the gas-liquid interface agent is completely dissolved to obtain a gas-liquid interface agent mother solution; Take the air microsphere stabilizer and the water, wherein the weight ratio of the air microsphere stabilizer to the water is 1:5 to 1:8, heat the water to 40 to 50° C. and mix it with the air microsphere stabilizer, soak the air microsphere stabilizer in water to swell it, and obtain a colloid by stirring, which is the mother solution of the air microsphere stabilizer; The mother solution of the gas-liquid interface agent and the mother solution of the air microsphere stabilizer are mixed in a weight ratio of 1:1 to 1:1.5 to obtain a mixed mother solution, and the mixed mother solution is diluted with 40 to 45 times the volume of water to obtain the air microsphere generating solution; Step 3: Preparation of high-concentration and high-fluidity tailings filling materials The ore dressing tailings pretreated in step 1 are introduced into a continuous mixer or a stirring tank for stirring. During the stirring process, the cementitious material is continuously added at a ratio of 6% to 10% of the weight of the ore dressing tailings by another conveying device. At the same time, the liquid-solid interface agent at a ratio of 0.1% to 1.0% of the weight of the cementitious material is continuously added into the above-mentioned continuous mixer or stirring tank through a metering and conveying device. Through continuous stirring, the ore dressing tailings, the cementitious material and the liquid-solid interface agent are gradually mixed and uniformly during the moving process to obtain a full tailings cementitious paste, and then the full tailings cementitious paste is collected in a pre-pump stirring tank; Using a liquid flow pump to extract the air microbead generation liquid and send it to an air microbead generator, and using the air microbead generator to obtain air microbeads; The air microspheres sprayed from the air microsphere generator are mixed into the whole tailings cement paste in the mixing tank before the pump, and the volume ratio of the whole tailings cement paste to the air microspheres is 10:1 to 10:3, so as to obtain a stable, rheological, non-bleeding, non-segregating high-concentration and high-fluidity whole tailings filling material; Step 4: Filling Relying on gravity or pumping force, the high-concentration and high-fluidity full tailings filling material is transported to the tunnel or mine pit to be filled through the filling pipeline; Step 5: Filling and Control Observations were conducted during the transportation of the high-concentration and high-fluidity full tailings filling material. The normal state of the high-concentration and high-fluidity full tailings filling material is no precipitation, no segregation, and no water seepage. After filling in place, precipitation and solidification will occur. A trace amount of water seepage is allowed, but obvious segregation is not allowed. By matching the ratio of the gas-liquid interface agent and the air microsphere stabilizer in step 2, the air microspheres will not burst before the high-concentration and high-fluidity full tailings filling material is filled in place, and will burst within 6 hours after filling in place.

10. The filling method according to claim 9, characterized in that: In step five, if it is observed that the air microspheres cannot be ruptured within 6 hours after the high-concentration and high-fluidity full tailings filling material is filled in place, the air microsphere scavenger is mixed into the outlet of the filling pipe. The amount of the air microsphere scavenger is 0.001‰ to 0.01‰ of the weight of the high-concentration and high-fluidity full tailings filling material. The more the amount used, the faster the air microspheres will rupture.